Bimbingan Teknis Penguatan Wirausaha Pemula di Kota Padang - Dika, Riri Putri; Sari, Vivi Puspita; Medina, Pinta (CV. ITTC INDONESIA, 2024)
Many people want to start a small business at home without a lot of capital, and many also don't understand what to do considering there are many limited capital for starting a business, either capital or knowledge. Through technical guidance, you can explore your ability to manage existing resources, human resources become a benchmark in developing entrepreneurship and business potential. Resources that are capable, competent and intelligent in using science and technology in processing business ideas, even more than that, require resources that can innovate to provide added value so that existing resources provide high economic value and are also able to maintain sustainability. This Technical Guidance provides a broad and varied learning experience by combining participants from various backgrounds and roles as well as interactive learning methods. This is very profitable, especially because Bimtek participants come from the general public who need guidance, support and inspiration. Providing participants with detailed entrepreneurial knowledge and materials can help them create an effective action plan for setting up a new business.